Harnessing Digital Literacy Practices of Undergraduate Pre-service English Language Teachers in Tanzania - Upor, Rose A. (Papers in Education and Development, 2022)
Abstract This paper examines undergraduate pre-service English language teachers ' digital literacy practices to establish whether their digital skills predict effective integration into language teaching and learning. A total of 410 undergraduate pre-service English language teachers enrolled in an education programme participated in the study. The findings revealed that the transfer of digital skills from non-academic to academic purposes was limited among the participants. According to the results, digital experience outweighed age as a factor in integrating technology into educational practices. Mobile devices were also frequently used to access the Internet for teaching and learning. From a pedagogical viewpoint, this study emphasises mobile literacy in universities, where efforts should be made to code transferable digital skills that may aid language teaching and learning. Keywords: digital learning resources, digital skills, preservice teachers, Tanzania, TPACK